Correction: Hormetic and transgenerational effects in spotted-wing Drosophila (Diptera: Drosophilidae) in response to three commonly-used insecticides. - Carrie Deans; William D Hutchison (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0271417.].